(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the epidemiological profile of leprosy in northeastern Brazil in the period 2016-2020. Methodology: This is a retrospective, descriptive study with a quantitative approach on the epidemiological profile of leprosy cases in northeastern Brazil in the period from 2016 to 2020, with data collected in the Notifiable Diseases Notification System from October to November 2021. Results: 67,070 cases of leprosy were diagnosed in the northeast region during the study period, with a predominance of males (56.2%), age group 40-49 (18.4%), the most operational classification. found was multibacillary (73.9%), with borderline clinical form (42.9%), most were new cases (79.5%) with most patients evolved to clinical cure (59.5%), with the majority of the degree of disability after cure being blank (48.5%) followed by degree zero (32.2%). Conclusion: The results show for health actions aimed at the early diagnosis of the disease and for the continuing education of health professionals.